2021
DOI: 10.3390/jmse9101088
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Polystyrene (PS) Microspheres in Short-Term Exposure to Gametes of the Sand Dollar Scaphechinus mirabilis (Agassiz, 1864) (Echinodermata, Echinoidea)

Abstract: Microplastic pollution appears to be one of the major environmental problems in the world today, and researchers have been paying special attention to the study of the impact of microplastics on biota. In this article, we studied the short-term effects of polystyrene micro-spheres on genome integrity using the gametes of the Scaphechinus mirabilis sand dollar with the comet assay method. This highly sensitive method allowed us to identify the level of genome damage in both gametes before and after short-term e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…Another endpoint analyzed in our study was the overexpression of ROS, an index of the oxidative stress state of cells. It is known that an imbalance between antioxidant and oxidant systems causes the uncontrolled release of radical molecules, which can react with macromolecules by oxidizing and degrading them through lipid peroxidation phenomena [74,75]. In our study, no evidence of increased ROS after 30 min of exposure was found, although in another study, significant ROS generation and subsequent oxidative stress were described after 5 h of exposure [55].…”
Section: Discussioncontrasting
confidence: 50%
“…Another endpoint analyzed in our study was the overexpression of ROS, an index of the oxidative stress state of cells. It is known that an imbalance between antioxidant and oxidant systems causes the uncontrolled release of radical molecules, which can react with macromolecules by oxidizing and degrading them through lipid peroxidation phenomena [74,75]. In our study, no evidence of increased ROS after 30 min of exposure was found, although in another study, significant ROS generation and subsequent oxidative stress were described after 5 h of exposure [55].…”
Section: Discussioncontrasting
confidence: 50%
“…The sand dollar S. mirabilis proposed as an object of study is widely distributed in the Far East region, and is well studied and sensitive to the impact of natural and anthropogenic factors [ 33 , 34 , 35 ]. The sand dollar S. mirabilis , as a typical representative of the class of sea urchins, throws out germ cells directly into sea water during the spawning period, where fertilization and further development of embryos and larvae take place.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the previous data, it has been observed that both MPs and NPs can induce DNA strand breaks, with the extent of the damage being influenced by their respective size and surface charge. Although the exact mechanism by which MPs/NPs induce DNA damage has yet to be fully understood, several investigations suggest that oxidative stress and physical interaction are pivotal in instigating DNA strand breaks by MPs and NPs [62,63]. Additionally, synthetic polymers may have low-molecular-weight fragments of mono-and oligomers, catalysts, artificial stabilizers and a variety of particular chemical additives such as (phthalates, bisphenol A, stabilizers, pigments, flame retardants and polychlorinated biphenyls (PCBs), each of which has genotoxic properties [64].…”
Section: Discussionmentioning
confidence: 99%